2017
DOI: 10.3892/ijo.2017.3875
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1/PTEN/PI3K signaling plays a critical role in the anti-proliferation effect of tetrandrine in human colon cancer cells

Abstract: The diagnosis and treatment for colon cancer have been greatly developed, but the prognosis remains unsatisfactory. There is still a great clinical need to explore new efficacious drugs for colon cancer treatment. Tetrandrine (Tet) is a bis-benzylisoquinoline alkaloid. It has been shown that Tet may be a potential candidate for cancer treatment, but the explicit mechanism underlying this activity remains unclear. In this study, we investigated the anticancer activity of Tet in human colon cancer cells and diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
(71 reference statements)
1
10
1
Order By: Relevance
“…These findings are consistent with our observation of significantly increased expression levels of STAT6 and STAT5B as a result of TGFβ1 activation. It is well established that the activation of the PI3K-Akt axis by TGFβ1 can trigger a wide range of metabolic and cellular effects in different cell types [48][49][50][51]. Consistent with our finding, the PI3K-Akt cascade has long been considered as one of the most significant Smad-independent regulatory route for MSC osteogenesis [52].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with our observation of significantly increased expression levels of STAT6 and STAT5B as a result of TGFβ1 activation. It is well established that the activation of the PI3K-Akt axis by TGFβ1 can trigger a wide range of metabolic and cellular effects in different cell types [48][49][50][51]. Consistent with our finding, the PI3K-Akt cascade has long been considered as one of the most significant Smad-independent regulatory route for MSC osteogenesis [52].…”
Section: Discussionsupporting
confidence: 91%
“…According to the above data, Tet can effectively suppress the growth and induce apoptosis in SW620 cells, so we next explored the underlying molecular mechanisms. Based on the reported that BMP9 is involved in the development of colon cancer, 26 we further explore BMP9 endogenous protein level in LoVo, HCT116, SW480, SW620, and FHC cell lines. Results showed that BMP9 mRNA level in cancer cells is much higher than that of FCH cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of mechanism, it was reported that some critical molecules or signaling pathways are associated with the pathogenesis of colon cancer, such as Wnt, EMT and TGF-β. 14 , 15 , 26 However, the explicit mechanism keeps unclear yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrandrine caused cell cycle arrest 45 and inhibited proliferation in colon cancer cells in vitro. [46][47][48] In addition, tetrandrine induced apoptosis in vitro and in vivo. 49,50 A previous study reported that tetrandrine inhibited the metastasis of CRC; 51 however, to the best of our knowledge, the molecular mechanism has yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%